INFLUENCE OF GUIDANCE AND COUNSELING ORIENTATION SERVICES ON LIFE SKILLS DEVELOPMENT AMONG SELECTED SECONDARY SCHOOLS IN MUDUUMA SUB-COUNTY, MPIGI DISTRICT. A CROSS-SECTIONAL STUDY. - Zawedde , Josephine; Kiyingi, Pio Frank (Student’s Journal of Health Research Africa, 2024)
Background Guidance and counseling services are a set of comprehensive programs and interventions designed to support individuals in their personal, social, educational, and career development. The study aims to assess the Influence of guidance and counseling orientation services on life skills development in secondary schools in Muduuma Sub-county, Mpigi District. Methodology A cross-sectional study utilizing both qualitative and quantitative research methods. Qualitative component involved obtaining graphs, and charts. Simple Random Sampling and Purposive Sampling were used. Results (56.1%) of the respondents were male while (43.9%) were female. The mean score for participants’ belief in the importance of the guidance and counseling Orientation services for personal development was M = 3.98 (SD = 0.981). Participants’ satisfaction with the information provided during the guidance and counseling Orientation services yielded a mean score of M = 3.44 (SD = 1.218). Participants indicated a mean score of M = 3.34 (SD = 1.146) for the effectiveness of the guidance and counseling Orientation services in addressing their specific needs and concerns. The guidance and counseling Orientation services were perceived as effective in preparing participants for academic challenges, with a mean score of M = 3.66 (SD = 1.249). The perceived effectiveness of the guidance and counseling Orientation services in enhancing well-being and overall development had a mean score of M = 3.49 (SD = 1.136). Conclusions Individuals who held a more favorable view of the Orientation services were also more likely to report higher levels of life skills. Recommendations The study recommended that the Ministry of Gender, Labour and Social Development and Ministries of Education should, through District Education Officers (DEOs) and inspectors, encourage head teachers to enhance Orientation services quality and consistency.